Physicochemical analysis and antioxidant activity of honey from three Malaysian stingless bees species - Khamsah Suryati, Mohd; Abd Jamil, Zakaria; Norazlin, Mohd Nasir; Nurhamizah, Ibrahim; Muhammad Muslim, Mohd Rodi (2019)
This study investigates physicochemical and antioxidant activity of raw and honey extract from three different species of Malaysian stingless bees. The methanol extract of commonly found Heterotrigona itama (EHI), Tetratgonula laeviceps (ETL) and Geniotrigona thoracica (EGT) was tested for their total flavonoid, total phenolic, moisture, ash, fat, protein and carbohydrate. Antioxidant activity through DPPH radical scavenging activity was also determined. Nutritional analysis of raw honey showed a comparable result. Analysis of total flavonoid and total phenolic for honey extract showed a significant difference between three species. In contrast, raw honeys did not show any significant differences between species. The antioxidant testing showed that the three honeys does not possess good antioxidant activity with inhibition lower than 50%. ETL showed the highest inhibition with IC50 of 37.8%, followed by EHI with 24.3% and EGT with 9.8% of inhibition, respectively. Thin layer chromatography analysis revealed the content of phenolic and flavonoids in all tested honey. The three extracts displayed a characteristic profile and vary from each other. This study revealed that bee species is important in determination of honey’s quality.